2017
DOI: 10.1039/c7ee00329c
|View full text |Cite
|
Sign up to set email alerts
|

“Protrusions” or “holes” in graphene: which is the better choice for sodium ion storage?

Abstract: The introduction of protrusions through P-doping into graphene is an effective strategy to enhance electrochemical performances in SIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(161 citation statements)
references
References 55 publications
1
158
0
2
Order By: Relevance
“…Previous works have demonstrated positively charged species in heteroatom doped carbons are active centers, [26,27] in this case,S ea toms.A dditionally,t he incorporation of larger atomic radius of Se atom could enlarge graphitic interlayer spacing and lead to structural strains and defects at the graphitic edges, [28,29] which is in favor of promoting the mass transportation efficiency in the graphitic layers and exposing numerous active sites for the HzOR. Previous works have demonstrated positively charged species in heteroatom doped carbons are active centers, [26,27] in this case,S ea toms.A dditionally,t he incorporation of larger atomic radius of Se atom could enlarge graphitic interlayer spacing and lead to structural strains and defects at the graphitic edges, [28,29] which is in favor of promoting the mass transportation efficiency in the graphitic layers and exposing numerous active sites for the HzOR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have demonstrated positively charged species in heteroatom doped carbons are active centers, [26,27] in this case,S ea toms.A dditionally,t he incorporation of larger atomic radius of Se atom could enlarge graphitic interlayer spacing and lead to structural strains and defects at the graphitic edges, [28,29] which is in favor of promoting the mass transportation efficiency in the graphitic layers and exposing numerous active sites for the HzOR. Previous works have demonstrated positively charged species in heteroatom doped carbons are active centers, [26,27] in this case,S ea toms.A dditionally,t he incorporation of larger atomic radius of Se atom could enlarge graphitic interlayer spacing and lead to structural strains and defects at the graphitic edges, [28,29] which is in favor of promoting the mass transportation efficiency in the graphitic layers and exposing numerous active sites for the HzOR.…”
Section: Resultsmentioning
confidence: 99%
“…[61,62] Density functional theory calculations for sodium adsorption revealed that each dopant (pyridinic/pyrrolic nitrogen, boron, phosphorus, fluorine) can lower the diffusion energy barrier by creating an electronic deficient system, and that codoping with two different heteroatoms shows a synergistic effect for improved capacity. [86] Luo et al first demonstrated the electrochemical storage of potassium in RGO for a capacity of 220 mAh g −1 at 5 mA g −1 , with a sloping voltage profile. For example, in Figure 6b, graphene with protrusions achieved a capacity of 374 mAh g −1 after 120 cycles at 20 mA g −1 , as compared to 211 mAh g −1 for graphene with holes.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[105] MWCNTs exhibit poorer cycling stability, along with less than half the sodium insertion capacity of SWCNTs, due to the less ordered internal environment, resulting in 30 mAh g −1 after 100 cycles. [86] Copyright 2017, The Royal Society of Chemistry. Energy Mater.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, graphene, a single layer of carbon atoms arranged in a hexagonal lattice, is an appealing material for photonics and electronics [23][24][25]. Conventional graphene materials can absorb photons from visible to infrared range [26,27] and exhibit a huge electrical mobility up to 200,000 cm 2 V −1 s −1 for a free sheet for both electrons and holes [28], which promote ultrafast conversion of photons or plasmons [29] to electrical currents or voltages for photo response.…”
Section: Two-dimensional Photodetectors Made Of Single-component Semimentioning
confidence: 99%